Nurses' smoking, alcohol and substance use behaviors intertwined with resilience patterns - Jarrad, Reem; AlHourani, Eman; Mahmoud, Naser; Malkawi, Adeeb; AL Fayoumi, Dua' (Jordan Medical Journal, 2025)
Background and Aims: Some nurses turn to non-adaptive behaviors including smoking, alcohol and substance use. This study aimed to assess nurses’ smoking, alcohol and substance use behaviors along with their intertwined resilience patterns. Method: Design. This was a cross-sectional correlational descriptive study where data were collected from 1000 hospital-based nurses. Analysis. Chi-square analysis was used to test the association between substance use and nurses' gender and type of healthcare sector. Student t-test examined the impact of resilience levels on substance use. Measurements. The outcome variable was substance use assessed by the ASSIST (McNeely J et al, 2016). Variables of gender, type of hospital and other socio-demographic variables were assessed by self-reported questionnaire. Resilience was measured by the Connor-Davidson resilience Scale (10-items) (Connor M & Davidson R,2003). Results: The highest rates of substance use among nurses was found in caffeinated drinks followed by smoking, hypnotics, alcohol, opioids, then others. The percentage of illicit drug use scored the least in cocaine (6.1%), then hallucinating agents (7%), cannabis (7.1%), stimulants (7.3%), inhaled substances (7.6%), and the highest score was for opioids (8%). Those rates where significantly reduced to 1.2, 1.5, 1.8, 1.3, 1.5, 1.6 % respectively, when regularity of consumption was taken in consideration. Gender played a role where males scored significant associations in favor of smoking, alcohol, cannabis and hypnotics over their female partners. Substance non-users scored higher in resilience mean scores than substance users. Conclusions: Traumatic experiences induce protective mechanisms to help nurses endure emotional pain. Some of those mechanisms include patterns of smoking, alcohol and forms of substance use. So, health care authorities should take nurses’ psychological well-being seriously and act proactively in building supportive and rehabilitative programs.